Assessing the Impact of Postoperative Radiation Therapy for Completely Resected Limited-Stage Small Cell Lung Cancer Using the National Cancer Database. Issue 2 (February 2016) - Wong, Andrew T.; Rineer, Justin; Schwartz, David; Schreiber, David
ABSTRACT: : Introduction: : Surgical resection is being increasingly used for early‐stage small cell lung cancer (SCLC). However, there are sparse data regarding the role of adjuvant therapies, particularly postoperative radiation therapy (PORT). We investigated the impact of PORT on survival after complete surgical resection for SCLC using the National Cancer Database. Methods: : There were 3017 patients diagnosed with nonmetastatic SCLC between 1998 and 2011 who underwent R0 sublobar resection, lobectomy, or pneumonectomy. Patients were stratified by the use of PORT, and only those who received a minimum dose of 45 Gy were included. The overall survival (OS) of patients based on PORT use were analyzed by Kaplan–Meier analysis and compared using the log‐rank test. Multivariate Cox regression analysis was used to identify factors associated with survival. Results: : For the entire study population, the 5‐year OS was significantly poorer with the addition of PORT (33.9% versus 40.6%; p = 0.005). When analyzed by subgroup, patients with pN0 stage had significantly decreased OS with PORT (39.3% versus 46.3%; p = 0.07) and patients with pN2 stage had significantly improved OS with PORT (29.0% versus 18.6%; p < 0.001). No differences in OS were observed in patients with pN1 stage. On multivariate analysis, the hazard ratio for PORT in pN0 disease was 1.36 (95% confidence interval, 1.09–1.70; p < 0.001) and the hazard ratio for PORT in pN2 disease was 0.60 (95% confidence interval, 0.45–0.80; p < 0.001). Conclusion: : The use of PORT was associated with a deleterious effect on OS in patients with pN0 disease but significantly improved OS in patients with pN2 disease.